GENDER DIFFERENCES ON STATE SELF-ESTEEM IN YOUNG ADULTS - Sobia Aftab ,Sofia Aslam (Pakistan Journal of Clinical Psychology, 2014)
Objective: The present study aimed at investigating differences among male and female young adults on the variable of State Self-Esteem and its three subscales i.e., Performance Self-Esteem, Social Self-Esteem, and Appearance Self-Esteem. Research Design: A Comparative Study. Place of Study: Various departments within Science and Arts Faculties of University of Karachi. Sample and Method: The sample consisted of 500 young adults recruited from two Faculties of University of Karachi, i.e. Science and Arts. The ages of the participants ranged from 18-25 years with the mean age of 21.97 (SD= 1.95) Representation of both genders was equal in the sample. The research measure used was Urdu Adapted Version of State Self-Esteem Scale[1] along with Demographic Form. t-test was employed for statistical analysis of the data. Results: Results indicate insignificant differences among male and female young adults on the variable of State Self-Esteem (t = -0.89; df = 498; p> .05) and its three subscales i.e. i.e., Performance Self-Esteem (t= -1.55; df = 498; p> .05), Social Self-Esteem (t= -.84, df=498, p>.05), and Appearance Self-Esteem (t= .89, df=498, p>.05). Conclusion: The findings of present study showed insignificant gender differences on state self-esteem, appearance state self-esteem, performance state self-esteem and social state self-esteem which may be the result of the augmented changes in cultural and societal roles of women and women.